Price-determination and -setting in global production networks of critical minerals: The London Metal Exchange, price reporting agencies and digital trading platforms - Aleksandra Wojewska; Cornelia Staritz; Bernhard Tröster (Austrian Foundation for Development Research (ÖFSE), 2023)
Despite frequent debates on commodity prices, limited attention has been paid to the processes, strategies and practices through which commodity prices are 'made' and related institutions and infrastructures. 'World commodity prices' are not passively 'discovered' but are outcomes of contested price-making processes. This paper assesses how prices are determined and how they are set along global production networks (GPNs) for the critical metals copper, cobalt and lithium that are undergoing shifts in the context of green transitions. Conceptually, we link concepts of extractive industries in GPNs with sociological approaches to price-making and an infrastructural perspective. While the London Metal Exchange (LME) has been the established price-determination institution for copper and a leading price reporting agency (PRA) benchmark exists for cobalt, there is contestation between PRAs to become the dominant benchmark for lithium with the potential emergence of digital trading platforms. These differences are explained by particular materialities of metals and territorialities of their networks interrelated with historically developed production and organizational structures and powerful physical as well as financial actors' interests. There are however ongoing struggles within and between price-determination institutions. Generally, there is a trend to more short-term benchmarks linked to derivative markets, driven by financial actors' interest in getting exposure to metal price developments and financialization processes at the LME. The related increased price volatility has uneven distributional consequences along GPNs and is problematic for actors with limited access to price risk management. Methodologically, the paper is based on trade and financial data and semi-structured interviews with price-determination institutions and GPN actors.
Keywords: 330; price-making; global production networks; critical minerals; financialization; commodity derivative markets